Seawater carbonate chemistry and sperm and adult biomarkers in the mussel Mytilus galloprovincialis in a multi-stressor context - Cuccaro, Alessia; Moreira, Anthony; De Marchi, Lucia; Meucci, Valentina; Soares, Amadeu M V M; Pretti, Carlo; Freitas, Rosa (PANGAEA, 2025)
This study investigated the combined impacts of UV-filters 4-methylbenzylidene camphor (4-MBC) and benzophenone-3 (BP-3), at ecologically relevant concentrations (1 and 10 µg/L), under two target pH levels (8.2 and 7.7, reflecting a ∆pH of 0 and -0.3 relative to the average pH at the sampling site), on the biochemical performance and male reproductive health of the mussel Mytilus galloprovincialis. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were provided by the author of the related paper (see Related to) to the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-02-17.
Keywords: Animalia; Behaviour; Benthic animals; Benthos; Bottles or small containers/Aquaria (<20 L); Coast and continental shelf; Laboratory experiment; Mediterranean Sea; Mollusca; Mytilus galloprovincialis; North Atlantic; Organic toxins; Other metabolic rates; Other studied parameter or process; Reproduction; Single species; Temperate